2016
DOI: 10.3389/fmicb.2015.01532
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities Vary between Sinuses in Chronic Rhinosinusitis Patients

Abstract: Chronic rhinosinusitis (CRS) is a common and potentially debilitating disease characterized by inflammation of the sinus mucosa for longer than 12 weeks. Bacterial colonization of the sinuses and its role in the pathogenesis of this disease is an ongoing area of research. Recent advances in culture-independent molecular techniques for bacterial identification have the potential to provide a more accurate and complete assessment of the sinus microbiome, however there is little concordance in results between stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 26 publications
(39 reference statements)
5
58
0
Order By: Relevance
“…The levels of Cyanobacteria in this study accounted for a very small relative abundance (< 1%). A different study, conducted by Joss et al (2015), reported Cyanobacteria at a much lower abundance than the Aurora study (< 2.4% relative abundance). Variation between studies in reported Cyanobacteria abundance is likely due to differences in sequence processing and taxonomic classification databases, highlighting the importance of using standardized sequence processing protocols.…”
Section: Healthy Sinonasal Microbiomementioning
confidence: 64%
See 1 more Smart Citation
“…The levels of Cyanobacteria in this study accounted for a very small relative abundance (< 1%). A different study, conducted by Joss et al (2015), reported Cyanobacteria at a much lower abundance than the Aurora study (< 2.4% relative abundance). Variation between studies in reported Cyanobacteria abundance is likely due to differences in sequence processing and taxonomic classification databases, highlighting the importance of using standardized sequence processing protocols.…”
Section: Healthy Sinonasal Microbiomementioning
confidence: 64%
“…This lack of understanding is due to many factors, including small sample sizes, inadequate stratification of cohorts, insufficient taxonomic resolution of gene-targeted sequencing data and a restricted focus on the presence/ absence of microbes (community diversity) rather than community interaction and function. Additionally, much of the bacterial research in this field is limited to culturebased approaches which may not capture the extensive community diversity within the sinonasal cavity (Joss et al, 2015;Hoggard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus was enriched in CRSwNP, supporting culture‐based studies that have found elevated S. aureus colonization rates in the MM and S. aureus enterotoxin (SAE)‐specific immunoglobulin E (IgE) antibodies in a subset of patients with high eosinophilic inflammation . Alloiococcus spp., also enriched in CRSwNP, have been detected in the sinuses of CRS and healthy controls, and co‐colonization with Staphylococcus , Streptococcus , and anaerobic taxa in the maxillary sinuses of CRS patients has been reported . While co‐colonization may play an important role in bacterial behavior modification, whether and how this organism contributes to sinus inflammation is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation comparing surface swab to tissue biopsy demonstrated no difference in the microbial diversity revealed by the two methods, suggesting that swabs may serve as an adequate sampling method [52], a finding that has since been confirmed by a number of other groups. A recent publication also investigated inter-sinus differences, although only one subject studied had all sinuses from both sides sampled [53]. The authors found that compared sinuses were identical using unweighted UniFrac comparisons, suggesting no difference in presence or absence of taxa between specimens; using weight UniFrac distances that account for relative abundance, they concluded that when taking inter-individual variation into account, differences between sample sites were quite low.…”
Section: Discussionmentioning
confidence: 99%